Robotic Process Innovation as Mediator between Technical Traits and Lean Supply Chain Performance: An Empirical study in Thailand - Natnaporn Aeknarajindawat (International Journal of Supply Chain Management, 2019)
Thailand is not just thriving due to its tourism but the country’s manufacturing sector is also leaning towards robotic process innovation. Such innovation is strengthening due to technological advancements and resulting in enhanced firms’ productivity. This idea of bringing robotic process innovation is action can be really helpful for lean processes in organizations. This study has aimed to check the role of direct and indirect usefulness of technological traits on lean supply chain performance in mediating role of robotic process innovation. Study has taken only those Thailand’s manufacturing organization in sample who have already included robotic processes in their production system and their employees have surveyed through questionnaire. CFA and SEM were used to analyze model fitness and hypotheses. Results have enlightened that Both direct and indirect usefulness have significant impact on lean supply chain performance and also flagged significant mediating role of robotic process innovation in same relationships. Novelty in this study has come due to including a unique outcome lean supply chain performance as an output of robotic process innovation and technical traits. This study has its implications for not only for manufacturing but service sectors too to adopt such robotic practices to improve their performance levels.